PENGEMBANGAN MODEL KURSUS WIRAUSAHA DESA PEMBIBITAN KARET UNGGUL UNTUK MENINGKATKAN KOMPETENSI BERWIRAUSAHA WARGA BELAJAR - Badawi Badawi; Sutaryat Trisnamansyah (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This research is grounded on the fact that a lot of civillians are unemployed as they do not have enough knowledge and skills to work. On the other side, the increasing number of conversions from horticulture plants to rubber plants has caused the people’s demand for top rubber seeds to increase too.This research therefore wanted to find out the type of KWD Model to increase the entrepreneurship competency of the learning participants. Based on this objective, this research developed correlational and differential research questions. The correlational investigation was needed to examine the contribution of the independent variables toward the dependent variable (the increase of the entrepreneurship competency) of the learning participants. Meanwhile the differential investigation was needed to examine the effectiveness of the model.The result of the research indicates there is a positive and significant contribution of the learning participant’s interest, achievement motivation, the learning participant’s participation, technical resourceperson’s competence, the training curriculum, the infrastructure and facilities, the intstructional process, and the executing institution toward the increase of the entrepreneurship competency of of the learning participants both individually or all together. The test of model effectiveness proves a positive and significant difference between the designed model and the existing model.